If you graph the two equations then you will find that they intersect at (-2,-2).
You then have to check your answer.
x=4y+6
(-2)=4(-2)+6
-2=-8+6
-2=-2
x-3y=4
(-2)-3(-2)=4
-2+6=4
4=4
Answer:
f
(
x
)
=
−
1
2
x
2
+
3
x
−
1
2
Explanation:
A quadratic function can be written in vertex form as:
f
(
x
)
=
a
(
x
−
h
)
2
+
k
where
(
h
,
k
)
is the vertex and
a
is a constant multiplier.
In our example the vertex
(
h
,
k
)
is
(
3
,
4
)
, so we can write:
f
(
x
)
=
a
(
x
−
3
)
2
+
4
Given that this passes through the point
(
1
,
2
)
, we must have:
2
=
a
(
1
−
3
)
2
+
4
=
4
a
+
4
Subtract
4
from both ends to get:
−
2
=
4
a
Divide both sides by
4
and transpose to find:
a
=
−
1
2
So our quadratic function can be written in vertex form as:
f
(
x
)
=
−
1
2
(
x
−
3
)
2
+
4
We can multiply this out and simplify as follows:
f
(
x
)
=
−
1
2
(
x
−
3
)
2
+
4
f
(
x
)
=
−
1
2
(
x
2
−
6
x
+
9
)
+
4
f
(
x
)
=
−
1
2
x
2
+
3
x
−
9
2
+
4
f
(
x
)
=
−
1
2
x
2
+
3
x
−
1
2
Step-by-step explanation:
PLZ MARK ME BRAINLYIST
y=4/3-x/6
Step-by-step explanation:
6y/6+x/6=8/6
y+x/6=4/3
-x/6 -x/6
y=4/3-x/6